Effectiveness of a Video-based Teaching Program on Knowledge and Attitudes Toward Stem Cell Therapy Among Nursing Students - Mahendra Kumawat (International Journal of Community Health Nursing And Practices, 2024)
Integrating stem cell therapy (SCT) into healthcare necessitates adequate training for nursing students to comprehend its principles and applications. This study evaluates the efficacy of a video-assisted teaching program (VATP) in enhancing knowledge and attitudes toward SCT among nursing students. A pre-test post-test quasi-experimental design was utilized with a sample of 100 nursing students. The participants were split into experimental and control groups. The experimental group received the VATP intervention, while the control group experienced traditional teaching methods. Knowledge and attitudes concerning SCT were evaluated using validated questionnaires both before and after the intervention. The results demonstrated a significant enhancement in knowledge (p<0.05) and attitudes (p<0.05) toward SCT in the experimental group after the intervention, in contrast to the control group. The VATP effectively enhanced the understanding of SCT principles, therapeutic applications, and ethical considerations among nursing students. The findings underscore the efficacy of VATP as a valuable educational tool for fostering comprehensive understanding and positive attitudes towards emerging healthcare technologies like SCT among nursing students. Incorporating innovative teaching methods like VATP can significantly contribute to preparing nursing students for future healthcare practices involving advanced therapies like SCT. Additional research is needed to examine the long-term retention and application of knowledge following the intervention.
Keywords: Knowledge; attitude; nursing students; stem cell therapy; video-assisted teaching program